Persepsi Nelayan Desa Bajo Dalam Menghadapi Perubahan Iklim (Studi Kasus: Nelayan Desa Bajo, Kecamatan Tilamuta) - Lole, Fikran; Nurfaika, Nurfaika; Liayong Pratama, M. Iqbal (-, 2025)
In general, fishing communities are considered one of the lower socioeconomic strata." Of course, not all fishermen are considered poor; there are many fishermen who are considered prosperous. This research aims to describe the perceptions of Bajo village fishermen regarding climate change. Research Location: This research will be conducted in Bajo Village, Tilamuta District, Bualemo Regency. Based on the central statistics agency, the population of this study consists of all the fishing community members obtained from BPS, totaling 399. Using the Slovin formula, with the number of fishermen in Bajo village being 399 and a margin of error of 0.05, the required sample size for this study is 199 fishermen in Bajo village, Tilamuta district. The data analysis method uses Data Analysis with the Miles and Huberman Model. The Miles and Huberman Model is applied by categorizing data from in-depth interviews and direct observations in stages to draw a conclusion. The results of this research in Bajo Village show that 75% of fishermen are aware of weather changes and their impact on fishing activities, but 52% do not yet understand the causes. Most of them only check the weather information once a week, and 24% rarely do so. The level of concern is high (90% expressed worry), and all respondents feel the need to change their way of thinking and acting. As many as 71% feel confident they can face climate change, but only 25% feel personally prepared. The adoption of new technology is very low (90% have never tried it). However, 40.5% support environmentally friendly fishing methods. Support from relevant parties is considered sufficient by the majority of fishermen, although some still feel under-supported. Most fishermen have more than 10 years of experience, and 65% believe that experience helps in preparing for weather changes. As many as 89% of fishermen believe that weather conditions are worsening, reflecting concerns about future climate impacts